THE CHALLENGES OF IMPLEMENTING ANTI MONEY LAUNDERING REGULATIONS IN THE BANKING SECTOR - Neharika; Yadav, Sanjay Kumar; Kadakia, Babita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper considers the challenges the banking industry faces in implementing AML rules; its focus will be on banks in India's Delhi and Uttar Pradesh. The paper has adopted a descriptive style of research; the major issues for AML compliance, such as the increasing complexity of money laundering techniques, changes in the regulatory environment, and inefficiencies of older systems, are identified. By using a standardized questionnaire, the researcher surveyed 200 respondents who belong to different types of banks and employment occupations. The study brings into light a number of grave issues such as ineffectual AML software, inadequate staffing, less participation of the clients in providing KYC data, lack of training, and imprecise protocols to detect suspicious transactions. It also finds that despite the fact that some of the AML procedures, such as reporting and updating of information in KYC exhibit high compliance levels, others, such as risk assessment, transaction monitoring, and record keeping need to be improved. According to the study, in order to improve AML compliance and the overall risk of money laundering within the banking sector, more resources, updated training curricula, more efficient software, and more transparent internal processes are needed.